2022
DOI: 10.1080/08897077.2021.2010252
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Multiple Naloxone Administrations for Opioid Overdose Reversals: A Review of the Literature

Abstract: Background A growing challenge in the opioid epidemic is the rise of highly potent synthetic opioids, (i.e., illicitly manufactured fentanyl [IMF]) entering the US non-prescription opioid market. Successful reversal may require multiple doses of naloxone, the standard of care for opioid overdose. We conducted a narrative literature review to summarize the rates of multiple naloxone administrations (MNA) for opioid overdose reversal. Methods: A MEDLINE search was conducted for published articles using MESH sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…At a 2016 FDA advisory committee meeting on community use of naloxone, there was general agreement that the risk of underdosing naloxone far outweighs the potential risk of precipitating opioid withdrawal; however, a consensus could not be reached on certain aspects related to dosing recommendations, due to a lack of evidence . There are conflicting data in the literature on whether higher or more doses of naloxone are needed in the current era of illicitly manufactured fentanyl . Most studies are single-center retrospective analyses, with limitations such as only including patients who survived an overdose or combining naloxone data from different routes of administration without considering the differences in the time profile of naloxone plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a 2016 FDA advisory committee meeting on community use of naloxone, there was general agreement that the risk of underdosing naloxone far outweighs the potential risk of precipitating opioid withdrawal; however, a consensus could not be reached on certain aspects related to dosing recommendations, due to a lack of evidence . There are conflicting data in the literature on whether higher or more doses of naloxone are needed in the current era of illicitly manufactured fentanyl . Most studies are single-center retrospective analyses, with limitations such as only including patients who survived an overdose or combining naloxone data from different routes of administration without considering the differences in the time profile of naloxone plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Intranasal naloxone products are sold in packages with 2 single-use nasal sprays and are approved for administration as a single dose with repeat doses every 2 to 3 minutes if the patient does not respond. Questions have emerged as to whether current naloxone dosing is adequate in the era of illicitly manufactured fentanyl, because of fentanyl’s potential to induce rapid respiratory depression and death and the observation that higher naloxone doses have been required . In addition, there are limited clinical data on repeat intranasal dosing, which can result in less-than-dose-proportional increases in plasma concentration with intranasal drugs …”
Section: Introductionmentioning
confidence: 99%
“…The high affinity of nalmefene at μ opioid receptors 19‐21 and its durability of action to reverse opioid‐induced respiratory depression 36 are attributes that, when used in an IN formulation producing rapid delivery of high plasma concentrations, have the potential to provide an important new intervention for victims of an opioid overdose used in a community setting. These pharmacological attributes may be especially important in an era when almost 90% of opioid overdose deaths are linked to synthetic opioids 1 and there is emerging evidence 4‐10 that higher doses of naloxone are needed to reverse a synthetic (eg, fentanyl) opioid overdose compared to both natural and semisynthetic opiates (eg, morphine and heroin).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In the face of a continued rise in opioid overdose deaths, the competitive μ opioid receptor antagonist naloxone remains the "gold standard" reversal agent. 1 Nonetheless, converging lines of evidence, ranging from preclinical studies [4][5][6] to clinical reports, [7][8][9] quantitative systems modeling, 10 and a CDC advisory warning indicate higher doses of naloxone are required to reverse an overdose produced by synthetics compared to either natural or semisynthetic opiates. Leaders of the National Institutes of Health 11 have called for the development of "stronger, longer acting formulations of antagonists…" in response to the rise in fatalities linked to synthetics, a position endorsed by The President's Commission on Combatting Drug Addiction and the Opioid Crisis.…”
mentioning
confidence: 99%
“…15,16 Real-world evidence indicates that a percentage of opioid reversals require multiple naloxone administrations (MNA) for successful reversal, and that the frequency of MNA is increasing over time. [17][18][19][20] Notably, patients presenting in emergency departments (EDs) with overdoses involving IMF have been found to have excessively higher levels of drug concentration, requiring prolonged naloxone infusions, multiple bolus doses, or higher than standard naloxone doses for reversal. 18,[21][22][23] Using the National Emergency Medical Services Information System (NEMSIS) data, Faul et al 19 indicated that the rate of MNA increased by 26%, from 14.5% in 2012 to 18.2% in 2015.…”
Section: Introductionmentioning
confidence: 99%